Chewing side, bite force symmetry, and occlusal contact area of subjects with different facial vertical patterns - Simone Guimarães Farias Gomes; William Custodio; Fernanda Faot; Altair Antoninha Del Bel Cury; Renata Cunha Matheus Rodrigues Garcia (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Craniofacial dimensions influence oral functions; however, it is not known whether they are associated with function asymmetry. The objective of this study was to evaluate chewing side preference and lateral asymmetry of occlusal contact area and bite force of individuals with different craniofacial patterns. Seventy-eight dentate subjects were divided into 3 groups according to the VERT index as follows: (1) mesofacial, (2) brachyfacial and (3) dolichofacial. Chewing side preference was evaluated using jaw tracking equipment, occlusal contact area was measured by silicon registration of posterior teeth, and bite force was measured unilaterally on molar regions using 2.25 mm-thick sensors. Statistical analysis was performed using ANOVA on Ranks, Student's t-test, and Mann-Whitney tests at a 5% significance level. Mesofacial, brachyfacial, and dolichofacial subjects presented more occlusal contact area on the left side. Only dolichofacial subjects showed lateral asymmetry for bite force, presenting higher force on the left side. No statistically significant differences were found for chewing side preference among all groups. Within the limitations of this study, it can be concluded that craniofacial dimensions play a role in asymmetry of bite force. ClinicalTrials.gov ID: NCT01286363.